Piroxicam attenuates 3-nitropropionic acid-induced brain oxidative stress and behavioral alteration in mice. (December 2014) - C, Jadiswami; H. M, Megha; Dhadde, Shivsharan B.; Durg, Sharanbasappa; Potadar, Pandharinath P.; B. S., Thippeswamy; V. P., Veerapur
Abstract 3-Nitropropionic acid (3-NP) is a fungal toxin that produces Huntington's disease like symptoms in both animals and humans. Piroxicam, a non-selective cyclooxygenase (COX) inhibitor, used as anti-inflammatory agent and also known to decrease free oxygen radical production. In this study, the effect of piroxicam was evaluated against 3-NP-induced brain oxidative stress and behavioral alteration in mice. Adult male Swiss albino mice were injected with vehicle/piroxicam (10 and 20 mg/kg, i.p.) 30 min before 3-NP challenge (15 mg/kg, i.p.) regularly for 14 days. Body weights of the mice were measured on alternative days of the experiment. At the end of the treatment schedule, mice were evaluated for behavioral alterations (movement analysis, locomotor test, beam walking test and hanging wire test) and brain homogenates were used for the estimation of oxidative stress markers (lipid peroxidation, reduced glutathione and catalase). Administration of 3-NP significantly altered the behavioral activities and brain antioxidant status in mice. Piroxicam, at both the tested doses, caused a significant reversal of 3-NP-induced behavioral alterations and oxidative stress in mice. These findings suggest piroxicam protects the mice against 3-NP-induced brain oxidative stress and behavioral alteration. The antioxidant properties of piroxicam may be responsible for the observed beneficial actions.